2013
DOI: 10.1152/ajprenal.00561.2012
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of N-type Ca2+channels in the fibrotic process of the kidney in rats

Abstract: type Ca 2ϩ channels are densely distributed in sympathetic nerves that innervate renal tubules. However, the role of N-type Ca 2ϩ channels in renal fibrosis remains unknown. To address this issue, we examined the difference between the effects of amlodipine (an L-type Ca 2ϩ channel blocker) and cilnidipine (a dual L/N-type Ca 2ϩ channel blocker) on fibrotic changes using a rat unilateral ureteral obstruction (UUO) model. The expression of both L-type and N-type Ca 2ϩ channels was significantly upregulated in U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…In addition, renal function was found impaired in UUO mice, which represented as increased levels of serum BUN and Cr and activities of GPT and LDH. For renal function of UUO models, different studies showed discrepant results and there is no reliable explanation for the discrepancy between these observations, and the clear reason still needs to be revealed. In our study, EGCG treatment prevented the tubular injury and restored the weight of obstructed kidney.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, renal function was found impaired in UUO mice, which represented as increased levels of serum BUN and Cr and activities of GPT and LDH. For renal function of UUO models, different studies showed discrepant results and there is no reliable explanation for the discrepancy between these observations, and the clear reason still needs to be revealed. In our study, EGCG treatment prevented the tubular injury and restored the weight of obstructed kidney.…”
Section: Discussionmentioning
confidence: 95%
“…Sequences of primers used in this study were as follows: β A subunit (sense, 5′-GGACCTAACTCTCAGCCAGAGATG-3′; antisense, 5′-TCTCAAAATGCAGTGTCTTCCTGG-3′), activin receptor type I (sense, 5′-AGTCGTGGTTCAGGGAGACA-3′; antisense, 5′-GAGTGGTGAGCTGAAGGTAG-3′), activin receptor type II (sense, 5′-TGTGAAATGAGTAGGGTGCC-3′; antisense, 5′-CCTTCATATCCGTGTTGCAG-3′), follistatin (sense, 5′-AAAACCTACCGCAACGAATG-3′; antisense, 5′-AGGCATTATTGGTCTGATCC-3′), and GAPDH (sense, 5′-CTACCCACGGCAAGTTCAAT-3′; antisense, 5′-TACTCAGCACCAGCATCACC-3′). Quantitative real-time PCR was performed as described previously [14]. …”
Section: Methodsmentioning
confidence: 99%
“…Indirect immunofluorescence staining was performed as described previously [14]. Briefly, frozen sections were washed in PBS, pretreated with 3% BSA-PBS for 1 h, and covered with primary antibody at room temperature for 1 h. After washing in PBS, sections were covered with a mixture of a fluorescence-labeled secondary antibodies and 4′-diamidino-2-phenylindole (DAPI).…”
Section: Methodsmentioning
confidence: 99%
“…69 Furthermore, L-type and N-type Ca 2+ channels are also upregulated in proximal tubules in UUO-OKs and their inhibition reduces TGF-β-mediated damage. 70 In this way, the ectopic expression in Madin-Darby canine kidney (MDCK) cells of parvalbumin, a cytosolic Ca 2+ -binding protein that possibly acts as an intracellular Ca 2+ shuttle, decreases the levels of the cytochrome c oxidase subunit 1 (COX1) and reduces mitochondrial mass. 71 Taken together, these data suggest that with UUO, there is a dysregulation in cytosolic Ca 2+ levels related to mitochondrial alterations and FA accumulation that plays an important role in the processes that favor renal fibrosis development.…”
Section: Mitochondrial Bioenergetics and Metabolic Alterationsmentioning
confidence: 99%